Training and health in gymnastics - Coppola, S.; Vastola, R.; Scatigna, M.; Fabiani, L. (Journal of Human Sport & Exercise, 2015)
The aim of this study was to analyze the training regimens of top level rhythmic gymnasts and their state of health. The research also focused on the information provided to the athletes about the relationship between sport and health. The sample consisted of fourteen high-level Italian gymnasts aged thirteen to eighteen. The instrument used was a structured medical history interview conducted by a doctor and a graduate student in physical education. A descriptive approach was used for the data analysis. The distribution of the variables collected in the group of athletes was studied. The results showed that, on average, throughout the year the athletes do from three to five hours of training five days a week, and travel from two to sixteen days a year for competitions. Given the age of the gymnasts in particular ten to fourteen who are under fifteen years old, it is a major undertaking. Gymnasts complained some non-specific symptoms, such as weakness and dizziness, with frequencies among more than half of the sample interviewed, especially close to competition dates. This finding suggests a reaction to stress, although the simple detection is insufficient for a correct interpretation. The data collected regarding the information provided to athletes on the risks associated with strenuous and demanding exercise shows that female athletes were not informed enough about the consequences. Self-assessment of health status is within the range of 6 to 10 (mean 7.7), despite the fact that they were not undergoing any kind of treatment at the time of the assessment and the medical history did not reveal any indication of disease or injury. In conclusion, based on the results obtained in this study it can be stated that: The young athletes need an approach to education / teaching that would enable them to deal consciously and adequately the competitive commitments, which are demanding in relation to the resources of pre-teens; The critical aspects regarding the non-specific signs and symptoms of health problems that emerged from the self-report and from the perception of health status scale need to be studied in further depth; The scientific debate on the problematic aspects with regards to the protection and promotion of the health of young athletes may provide those elements of knowledge, health education and support to growth, which can improve the overall management and self-awareness of the athlete without compromising the performance.